Purification and Characterization of Cinnamoyl-Coenzyme A:NADP Oxidoreductase in Eucalyptus gunnii. - Goffner, D. (1994)
Cinnamoyl-coenzyme A:NADP oxidoreductase (CCR, EC 1.2.1.44), the entry-point enzyme into the monolignol biosynthetic pathway, was purified to apparent electrophoretic homogeneity from differentiating xylem of Eucalyptus gunnii Hook. The purified protein is a monomer of 38 kD and has an isoelectric point of 7. Although Eucalyptus gunnii CCR has approximately equal affinities for all possible substrates (p-coumaroyl-coenzyme A, feruloyl-coenzyme A, and sinapoyl-coenzyme A), it is approximately three times more effective at converting feruloyl-coenzyme A than the other substrates. To gain a better understanding of the catalytic regulation of Eucalyptus CCR, a variety of compounds were tested to determine their effect on CCR activity. CCR activity is inhibited by NADP and coenzyme A. Effectors that bind lysine and cysteine residues also inhibit CCR activity. As a prerequisite to the study of the regulation of CCR at the molecular level, polyclonal antibodies were obtained.